SISTEM KONTROL PADA LEMARI PENITIPAN HELM BERBASIS INTERNET OF THINGS (IOT) MENGGUNAKAN ENERGI SURYA - Gerardus Kristo Prima; Pajri Harnedi; Sulistyo, Eko; Surojo (Politeknik Manufaktur Negeri Bangka Belitung, 2024)
Nowadays the use of motorbikes can no longer be avoided. Helmets are safety equipment that must be used by all groups, especially adults, especially students. Not only adults, but children also know how important it is to use a helmet safely. Helmet loss incidents often occur on every campus due to student negligence. Therefore, it is necessary to create a tool that can control the helmet storage cupboard for students so that they can recognize the locker key automatically via IoT, namely the application. The implementation method in working on this final project is to carry out tests on each helmet locker using an application to reduce the occurrence of helmet loss. The system that has been developed is able to control lockers with an average delay time of around 1.2 seconds.